Pengalaman Komunikasi Bagi Fandom POLCA - Fauziyyah, Khoirunnisa; Silvia, Putri Jasmin; Pandora, Farisya Tsani; Anzani, Kinanggih; Aryanti, Marsela Pretisa; Abidin, Zainal (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study presents a phenomenological exploration aimed at delving into the experiences of members within the Polca community, a fandom centered around enthusiasts of on-screen couples from dramas or films. Employing a qualitative approach with open-ended interviews, data were analyzed to identify the motivations, experiences, and perceptions of members regarding their affiliation with this community. The findings reveal that membership in the Polca community entails multifaceted impacts on its members, including heightened social connections and increased awareness of social issues such as sexuality. However, members also encounter stigma and discrimination from the broader society, particularly those originating from less supportive environments. The discussion highlights the significance of support and inclusivity within the Polca community in fostering a safe and supportive environment for its members, as well as exploring challenges and opportunities for social change through membership in this community. Recommendations are put forth to enhance member experiences and community contributions to society, including strengthening support and inclusivity, advocating for equality, raising public awareness, developing resources and support systems, and collaborating with external entities. This study provides valuable insights into the dynamics of membership within the Polca community and its broader social implications.